Implementasi Pembelajaran Tematik Terpadu Berdasarkan Kurikulum 2013 di MIN Tempel Sleman Yogyakarta - Sekarinasih, Anggitiyas (J-PGMI: Jurnal Pendidikan Guru MI, 2021)
In general, this study aims to describe the implementation of the 2013 curriculum seen from the integrated thematic learning planning process, the implementation of the learning process and the results seen from the assessment process based on the 2013 curriculum carried out by teachers at Madrasah Ibtidaiyah Negeri Tempel Sleman Yogyakarta. This research is a qualitative field research, that is, research that uses information obtained from the research objectives, hereinafter referred to as informants or respondents through data collection instruments such as in-depth interviews, participatory observation and documentation methods. As for the qualitative data analysis process in this study using data analysis proposed by Miles and Hubermen, namely activities in qualitative data analysis are carried out interactively and continue to completion, so that the data is saturated. The results of this study indicate that the preparation and implementation of integrated thematic learning based on the 2013 curriculum at Madrasah Ibtidaiyah Negeri Tempel Sleman Yogyakarta is broadly in accordance with government regulations, namely the preparation is designed in the form of RPP, where the learning planning includes the preparation of lesson plans, media preparation and learning resources, and learning assessment tools. For the implementation of the learning process in general, learning with a scientific approach consists of observing, asking questions, gathering information, associating, and communicating. Meanwhile, the results of the implementation of integrated thematic learning can increase student learning outcomes seen from the aspects of attitudes, knowledge, and skills. Besides that, it is also able to create conducive learning, namely a pleasant learning atmosphere, increase student activity and motivation, and foster student discipline.